EXTH-17. LOCAL DELIVERY OF CYTOKINES AND SYNTHETIC IMMUNOMODULATORS INCREASES T CELL INFILTRATION AND SIGNIFICANTLY IMPROVES SURVIVAL IN A POORLY IMMUNOGENIC MODEL OF GLIOBLASTOMA. (9th November 2020) - Haddad, Alexander; Spatz, Jordan; Collins, Sara; Pereira, Matheus; Gill, Sabraj; Montoya, Megan; Chuntova, Polly; Young, Jacob; Mummaneni, Nikhil; Kasahara, Noriyuki; Aghi, Manish
Abstract: BACKGROUND: Severe local and systemic immune suppression in glioblastoma (GBM) contributes to the failure of single-agent immunotherapies in clinical trials. In this study, we evaluated the efficacy of locally delivered combination immunotherapy in a poorly immunogenic murine GBM model. METHODS: Immunomodulators used in these studies included: IL-15 and IL-7 (T cell activation), LIGHT (T cell tumor infiltration), FLT3L (dendritic cell maturation/proliferation), a surface T cell engager (T cell killing of tumor cells), and a bispecific PD-L1/T cell engager (T cell killing targeted to PD-L1-expressing cells). We first assessed T cell-mediated cytotoxicity in vitro against SB28, a poorly immunogenic murine GBM cell line, after expressing these immunomodulators in combination. Next, tumor growth inhibition in vivo was evaluated in syngeneic C57BL/6 mice, initially by establishment of intracranial tumors with pre-transduced SB28 cells, and subsequently by delivering these immunomodulators to pre-established naïve SB28 tumors using neural stem cells (NSCs) and retroviral replicating vectors (RRV). RESULTS: SB28 cells transduced with immunomodulators activated dose-dependent T cell-mediated cytotoxicity in vitro . Mice with pre-transduced intracranial SB28 gliomas showed significantly longer survival (minimum survival: 60 days, long-term survival in 57% of mice) vs. control mice (median survival: 20 days) (p< 0.001), and significantly increased tumor infiltration of CD4+ and CD8+ T cells. NSC- and RRV-mediated immunomodulator delivery to pre-established SB28 gliomas also resulted in significantly increased survival of treated mice vs. controls (median survival: 31 days vs. 22 days, p< 0.001). Immunomodulator-treated tumors again showed significantly increased infiltration of CD4+ and CD8+ T cells, along with decreased CD11b+ cell infiltration. CONCLUSIONS: A novel combination therapy for GBM immunotherapy activated T cell killing of SB28 GBM cells in vitro and achieved a significant survival benefit in vivo, associated with anti-tumor alterations to the GBM tumor microenvironment. Further studies to optimize the efficiency of combinatorial immunomodulator delivery are currently underway.